PENGARUH PENDIDIKAN DAN PELATIHAN (DIKLAT) TERHADAP KOMPETENSI KERJA APARATUR di SEKRETARIAT DAERAH KOTA TOMOHON - PUNU, ANGELIA SINTIA (Sam Ratulangi University, 2014)
Education and training is very important factor for improving the knowledge,skills,attitudes,andbehavior of government officials,so it has a working competence in accordance with the duties and positions.This study is intended to determine whether there is an influence of education and training for the competenceof personel working in the secretariat of tomohondistrick.Methods of research using quatitative methods that are koresional. Data sources are as many as 40research personel who were randomly taken from 125 people at secretariat of tomohon district. Data collectionusing questioner and help with interview tecniques. Analysis is a statistical used analysis linear regression andcorrelation moment product.The statistical analysis shows (1) the regression coefficient of the variables of education and traningof personnel working complence is positive and significant. (2) correlation coefficient of determination andthe power of education and traing variables to work competence of personnel is high and significant.Based on the results of the study concluded that education and training has a positive and significanteffect on the competence of personnel working in the secretariat of tomohon district.Based on the conclusion of the study suggested (1) education and training for personnel in thesecretariat of tomohon district need to be improved, especially the education and training of leacnical andfunctional, so that the budget allocation for education and training programs need to be improved. (2)education and training programs for personnel to be fully focused on the principle of correspondence betweenthe level of education and traing to the needs of the real objective and the task execution at all levels of theorganization, so that the provison of education and training should be based on the job description and jobanalysis are accurate and precise.Key words : education and training, competence job.